2018
DOI: 10.1016/j.celrep.2018.06.052
|View full text |Cite
|
Sign up to set email alerts
|

OX40 Costimulation Inhibits Foxp3 Expression and Treg Induction via BATF3-Dependent and Independent Mechanisms

Abstract: SUMMARY Naive CD4+ T cells can be converted to Foxp3+ T regulatory cells (Tregs) in the periphery (iTregs), where induction of Foxp3 gene expression is central to Treg differentiation. OX40 signaling is known to inhibit Foxp3 expression and Treg induction, but the underlying mechanisms remain poorly defined. Here, we found that OX40 costimulation activates two distinct molecular pathways to suppress Foxp3 expression in freshly activated naive CD4+ T cells. Specifically, OX40 upregulates BATF3 and BATF, which p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 48 publications
7
66
0
Order By: Relevance
“…In fact, the transcription factor BATF3 can repress Foxp3 expression by recruiting the histone deacetylase Sirt1. 56 This finding is consistent with other reports that p50 is capable of interacting with HDAC proteins in different cell types. 57,58 It should be noted that the p50-mediated chromatin remodeling process is independent of the transcriptional activity of p50.…”
Section: Nf-κb Family Members As Chromatin Modifierssupporting
confidence: 93%
“…In fact, the transcription factor BATF3 can repress Foxp3 expression by recruiting the histone deacetylase Sirt1. 56 This finding is consistent with other reports that p50 is capable of interacting with HDAC proteins in different cell types. 57,58 It should be noted that the p50-mediated chromatin remodeling process is independent of the transcriptional activity of p50.…”
Section: Nf-κb Family Members As Chromatin Modifierssupporting
confidence: 93%
“…However, we detected impaired suppressive function rather than defective Treg expansion in our in vitro culture system. It has been previously reported that Tregs display high levels of OX40 on their surface and enforced expression of OX40L on APCs or agonistic triggering of OX40 disrupts Treg suppressor functions and leads to reduced survival (54)(55)(56). Indeed, blocking of OX40L on the surface of CD83-deficient DCs reversed the enhanced T cell proliferation, which therefore may rely on mitigated Treg suppression by OX40-OX40L interaction.…”
Section: Discussionmentioning
confidence: 95%
“…Both GITR and OX40 have well-established roles in Treg development in the thymus (Mahmud et al, 2014), but their roles in mature Tregs are unclear and nuanced. Some reports show that ligation of OX40 or GITR decreases Treg suppressive capability (Cuzzocrea et al, 2005;Kitamura et al, 2009;Shimizu et al, 2002;Vu et al, 2007;Xiao et al, 2012;Zhang et al, 2018) with others reporting a benefit for Treg proliferation and function (Ephrem et al, 2013;Kinnear et al, 2013), possibly related to the kinetics of receptor stimulation. We found that although the GITR-and OX40-CAR Tregs provided an intermediate GVHD survival benefit at the high Treg:PBMC ratio in vivo, neither CAR was able to stimulate proliferation or strong activation of Tregs in vitro.…”
Section: Previous Reports On the Function Of 4-1bb In Tregs Have Beenmentioning
confidence: 99%